ଶ୍ରୀମଦ୍‍ ଭାଗବତ - Jagannath Das (Odisha Sahitya Akademi Bhubaneswar, 2022)
Odia Bhagavat by Jagannath Dasa is not only his Magnum -opus but the greatest creation of Odia literature which shaped the standard Odia language. A few books in the whole of Indian literature that can be compared in test and in pervasive influence like Odia Bhagavat. By presenting to the people the poet induced all classes of men of his country to cultivate Odia language the benefit which Jagannath Das has conferred open his countrymen is immense how the moral ideas preached by him in the book have module the character of many millions of men. What makes Jagannath Das’s Bhagavat is popular with Oriya masses as is the English Bible among the English speaking people is just what is called the biblical idiom in English Jagannath Das’s Bhagavat is a miracle of translation. Its accurate, precise and clear. General Aroma of sanctity it's soft fluency its quite dignity and the sublime of high moral in spiritual life it reaches so straight into the hearts of readers of all the books in Odia literature it is the Bhagavat of Jagannath Das that one comes across the mysterious and devotional feeling. Combining the classical Sanskrit with Odia idioms and phrases, choosing only what is elegant and rhythmic diction instinctively carrying more for beauty of expression than for pedantic accuracy and ser charging the whole subtle mystic atmosphere in which details may not be clear at once, but the totality is charming to the mind as well as to the ear. Jagannath Das has left behind a style in Odia which for its chastity , elegance, dignity and beauty still remains inimitable among the masses of Odisha.
Srimad Bhagabata
Keywords: Odia